Emotional appeals in marketing: A systematic literature review and research agenda - Mirmahdi Komejani, S. M.; Bilro, R. G.; Loureiro, S. M. C. (Italian Journal of Marketing, 2026)
This study presents a comprehensive synthesis of the literature on emotional appeals in marketing, conducted through a systematic review of 136 peer-reviewed articles retrieved from the Web of Science and Scopus. Using data mining and topic modelling techniques in R, the analysis uncovers 14 latent thematic clusters that reflect the evolving role of emotions across domains such as advertising, branding, consumer engagement, and digital media. Beyond mapping existing contributions, the study addresses conceptual fragmentation and terminological inconsistencies by proposing an integrative framework that connects emotional constructs across strategic and operational marketing contexts. A key outcome of this review is the development of a structured research agenda that identifies underexplored areas, such as collective emotional processing, real-time engagement on digital platforms, and emotional branding in emerging sectors, and offers direction for future theoretical and empirical work. Additionally, this paper offers a framework structured using the TCM (Theory–Characteristics–Methodology) model, which helps position the identified gaps and suggests actionable pathways for advancing research in the field. By consolidating scattered insights and systematising future research priorities, this study contributes as a roadmap for scholars seeking to deepen their understanding of how emotions influence the dynamics in the increasingly complex marketing environment.